Actors of Becoming. Aristotle and the new mimesis’ profils (Nóema, 2013)
A new critical reading of Aristotle’s Poetics help us to focus in a different way the debate about Aritotleism and anti-Aristotleism in XX century’s theatre. The Author thinks that a new reading of Poetics could help to understand that contemporary theatre is going towards a “neodramatic” stage and not a “postdramatic” one, that the theory of «essential actions» could not be referred only to prose and realistic theatre, and, first of all, that the question concerning the dynamic arts should be considered as a central educational topic.
Keywords: Aristotle; theatre; mimesis; Pierluigi Donini; dynamic arts; education; catharsis; actors; Brecht; Grotowski